Jarh wa Ta'dil Analysis Study: Biographical Analysis of Ibn Shihab Az-Zuhri's Hadith History - Ujang Sahid; Dadah (al-Afkar, Journal For Islamic Studies, 2025)
This case The objective of the study is to conduct a thorough analysis of biography of a prominent hadith transmitter, namely Ibnu Shihab Az-Zuhri, in the context of Islamic hadith scholarship. Ibnu Shihab Az-Zuhri is Recognized as one of the most influential hadith Academics in his generation additionally is one of the main intermediaries in conveying the hadith legacy of the Prophet Muhammad SAW to the next generation.In this study, we will present a comprehensive review of Ibn Shihab Az-Zuhri's background, education, method of narration, and scientific contribution to the dissemination and understanding of hadith. We will explore relevant primary sources, including hadith books and biographical literature, and evaluate the reliability and credibility of existing information.Through an analytical approach, we will describe various aspects of Ibn Shihab Az-Zuhri's scholarship, including narration style, assessment criteria, and the influence of his contribution on the development of hadith science. We will also highlight his role in transmitting the Prophet's traditions to subsequent generations, as well as his influence on the development of hadith thought.By deepening understanding of Ibn Shihab Az-Zuhri's biography as a hadith transmitter, This study is anticipated to provide a substantial contribution to the study of Islamic hadith science. Apart from that, the results of this Analysis has the potential to also be an important reference for researchers and hadith reviewers in understanding the crucial historical and scientific context of hadith transmitters in the Islamic tradition.